Sonata for Two Pianos and Percussion: Percussion Part - BARTOK, Bela (Hawkes& Son(London) td, 1942)
Percussion I : 3 Timpani, Side drum with snares, side drum withouyt snares, trianle, tam-tam, cymbal suspended, pair of cymbals.Percussion II : xylophone, bass drum, side drum with snares, side drum without snares, trianle, tam-tam, cymbal suspended, pair of cymbals